Fibroblast-Activated Protein Inhibitor PET/CT: Cancer Diagnosis and Management - Kuyumcu, Serkan; Sanli, Yasemin; Subramaniam, Rathan M. (Frontiers in Oncology, 2021)
Fibroblast activation protein (FAP), overexpressed on cancer-associated fibroblasts (CAF), is a novel target for molecular imaging of various tumors. Recently, the development of several small-molecule FAP inhibitors for radiolabeling with 68Ga has resulted in the emergence of studies evaluating its clinical role in cancer imaging. Preliminary findings have demonstrated that, in contrast to radiotracers taking advantage of cancer-specific targets such as PSMA and DOTATATE, FAPs as a target are the most promising that can compete with FDG in terms of widespread indications. They also have the potential to overcome the shortcomings of FDG, particularly false-positive uptake due to inflammatory or infectious processes, low sensitivity in certain cancer types, and radiotherapy planning. In addition, the attractive theranostic properties may facilitate the treatment of many refractory cancers. This review summarizes the current FAP variants and related clinical studies, focusing on radiopharmacy, dosimetry, and diagnostic and theranostic applications.